Access for all the future for Afghanistan an interview with Shaharzad Akbar . (Journal of International Affairs, 2013)
“Shaharzad Akbar’s journey to college was not an easy one. When she was eleven, the Taliban regime banned girls from going to school in Afghanistan. As a result, her family moved to Pakistan so she could continue with her studies. In 2002, when she was fifteen, the Back to School Campaign–a joint initiative by the United Nations and the Afghan Government–made her return possible. Later, Akbar would become the first Afghan woman to study at Oxford University and founded Afghanistan 1400, a young political movement that advocates for reforms and change in the country. In an interview with the Journal, Shaharzad Akbar spoke about the future of Afghanistan, the agenda her organization is pursuing, and the participation of women in this process.”